Image optimisation and dose reduction in computed radiography: pa chest and contrast detail phantom - Ahmad Radzi, Halimatussa’diah; Wan Long, Syarifah Fatmawati; Norddin, Narina; Mat Jusoh, Mohammad Amir Hakim; Ab. Aziz, Nurfaizatul Aisyah; Mohd Kasiram, Nur Zaira (unpublished, 2015)
Chest x-ray examination nowadays commonly performed using computed radiography (CR) system. This system allows post processing functions which manipulate the digital image. With these functions, too high radiation exposure can still produce acceptable images. Thus there is a tendency for radiographers to use higher exposure when using CR system. This research is carried out to study the adequate exposure factors (kVp and mAs) and the appropriate filtration thickness that could produce acceptable image quality of chest images in CR. It was carried out by exposing phantoms with different mAs exposures. Apart from that, different filtration thickness were also studied. In conclusion, this research finds out that lower mAs settings for chest x-ray can be used and the radiation exposure given to patient can be reduced extensively. Moreover, the radiographers should consider using filtration while performing the examination as there is no significant different in image quality when using the filtration and not using it.